The Effect of The Strength of Extremity and Motivation on Forward Roll of Achievement Learning - Syahruddin, Syahruddin; Latuheru, Ricardo Valentino (Universitas Negeri Semarang (Unnes), 2019)
The aims this research to determine whether there is influence of upper extremity strength, lower extremity strength and motivation on forward roll of achievement learning. The type of this study is a correlational survey involving independent variables consisting of upper extremity strength, lower extremity strength and motivation while the dependent variable is forward roll of achievement learning. The research sample was 40 students from SMK Layoa Bantaeng who were taken by purposive random sampling. The research instrument was arm muscle strength test using push and pull dynamometer, leg muscle strength test using leg dynamometer, and motivational questionnaire as well as forward roll process instruments. The results showed that there was a significant effect of upper extremity strength on forward roll of achievement learning (p <0.05), there was a significant effect of lower extremity strength on forward roll of achievement learning <0.05), there was a significant effect of motivation on forward roll of achievement learning (p <0.05) and there is a significant effect together of upper extremity strength, lower extremity strength and motivation on forward roll of achievement learning (p <0.05).